2020
DOI: 10.1177/1367006920909902
|View full text |Cite
|
Sign up to set email alerts
|

To mix or not to mix: Parental attitudes towards translanguaging and language management choices

Abstract: Aim and objectives: The present study investigates parental language beliefs and management among French-English bilingual families in the UK. It addresses the following two research questions. (a) What are parents’ attitudes towards translanguaging and beliefs about effective language management? (b) Do these beliefs and attitudes translate into language separation strategies versus flexible language practices? Design/methodology: This paper reports part of the results of a mixed-method study consisting of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 71 publications
5
18
0
Order By: Relevance
“…However, in everyday practice, they did the complete opposite and practiced TL, often mixing together Vietnamese and the minority language spoken at home as well as practicing other aspects of TL (Nguyen, 2019). Similarly, results of the current study further support previous research which has found that although parents state that their children being bilingual is very important to them, the actual FLP they implement in their homes is often inconsistent and uncertain (Lee et al, 2021;Piller & Gerber, 2021;Wilson, 2021). The current literature reveals the salient influence of parental decisions regarding FLP which differ depending on each family's varying needs and contexts (Lee et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, in everyday practice, they did the complete opposite and practiced TL, often mixing together Vietnamese and the minority language spoken at home as well as practicing other aspects of TL (Nguyen, 2019). Similarly, results of the current study further support previous research which has found that although parents state that their children being bilingual is very important to them, the actual FLP they implement in their homes is often inconsistent and uncertain (Lee et al, 2021;Piller & Gerber, 2021;Wilson, 2021). The current literature reveals the salient influence of parental decisions regarding FLP which differ depending on each family's varying needs and contexts (Lee et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…For example, when an individual has the ability to use both English and Korean, it was believed and strongly encouraged that the two languages should not be mixed or used together while communicating. Later on, many researchers began to take on a more heteroglossic view of bilingualism which supports the concept that bilinguals do not possess a separate compartment for each language but rather utilize simultaneously an infinite number of various forms and signs of languages in the linguistic repertoire to make sense of and communicate with individuals in the world around them (Wilson, 2021). The theoretical framework for this study draws from this heteroglossic perspective of bilingualism in which emergent bilingual speakers utilize their full linguistic repertoires from their two languages in order to navigate and make sense of a multilingual world (Higgins, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, numerous studies have explored the bilingual or multilingual policy in various countries and regions such as France [34], Cameroon [35], and the Arabian Peninsula [36]. Other topics in this line of research include bilingualism or multilingualism policy and politics [37,38], bilingual language policy in classrooms [39,40], bilingual language policy in universities [41,42], and bilingual language policy in family [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Outside community language schools, there is no empirical data on how communities make language mixing efforts on heritage language maintenance except the speech and song contests held by Tamil diasporas mentioned by Canagarajah (2012). In contrast, 6 articles report the role of language mixing in family heritage language learning even though they are not as many as studies in educational settings (Canagarajah, 2012;Ghimenton, 2015;Higgins, 2019;Kwon, 2019;Song, 2016;Wilson, 2020). As a microcosm, family plays an essential role in minority language maintenance and revitalization (Fishman, 1970).…”
Section: Language Mixings In Family and Communitymentioning
confidence: 99%